Association of Maternal Influenza Vaccination During Pregnancy With Early Childhood Health Outcomes. Issue 12 (December 2021) - Mehrabadi, Azar; Dodds, Linda; MacDonald, Noni E.; Top, Karina A.; Benchimol, Eric I.; Kwong, Jeffrey C.; Ortiz, Justin R.; Sprague, Ann E.; Walsh, Laura K.; Wilson, Kumanan; Fell, Deshayne B.
Abstract : (Abstracted from JAMA 2021;325:2285–2293) Vaccination for seasonal influenza is an important health intervention, even for pregnant women. Influenza vaccination helps to reduce the risk of severe influenza illness for the mother and child.